Resveratrol Confers Vascular Protection by Suppressing TLR4/Syk/NLRP3 Signaling in Oxidized Low-Density Lipoprotein-Activated Platelets - Xue, Yun (Oxid Med Cell Longev, 2021)
This study investigated the effect of resveratrol on Toll-like receptor 4- (TLR4-) mediated matrix metalloproteinase 3 (MMP3) and MMP9 expression in oxidized low-density lipoprotein- (ox-LDL-) activated platelets and the potential molecule mechanism. Human platelets were used in the present study. The results showed that resveratrol suppressed TLR4, MMP3, and MMP9 expression in ox-LDL-activated platelets. The TLR4 inhibitor CLI-095 also inhibited MMP3 and MMP9 expression and secretion in ox-LDL- and lipopolysaccharide- (LPS-) activated platelets. The combination of resveratrol and CLI-095 synergistically suppressed MMP3 and MMP9 expression in ox-LDL- and LPS-activated platelets. These findings suggest that the resveratrol-induced inhibition of MMP3 and MMP9 expression is linked to the suppression of TLR4 activation. Resveratrol also suppressed spleen tyrosine kinase (Syk) phosphorylation and nucleotide-binding domain leucine-rich repeat containing protein 3 (NLRP3) expression and IL-1β secretion in ox-LDL- and LPS-treated platelets. The coimmunoprecipitation results showed that resveratrol inhibited the binding of Syk and NLRP3. Finally, resveratrol reduced vascular senescence cells and the expression of TLR4, MMP3, and MMP9 and prevented alterations of vascular structure in 52-week-old mice. Our findings demonstrated that resveratrol decreased inflammatory protein expression and improved vascular structure in aged mice. Resveratrol inhibited the expression of TLR4 and secretion of MMP3, MMP9, and IL-1β. The mechanism of action of resveratrol appears to be associated with the inhibition of TLR4/Syk/NLRP3 activation in ox-LDL-activated platelets.